EFEKTIVITAS HARGA ZONA NILAI TANAH PADA KANTOR PERTANAHAN TERHADAP NILAI TRANSAKSI DALAM AKTA JUAL BELI TANAH YANG DIBUAT OLEH PEJABAT PEMBUAT AKTA TANAH DI KOTA PALEMBANG - Heriyanto Heriyanto (Universitas Sriwijaya, 2016)
Zones Price of Land is a polygons which illustrate the relative value of the same land from a set of plot in it, which is the limits could be imaginary or real according to the real use of the land and have a difference price between one another based on officers analysis with the market price comparison method and the fee determined by the officers of the land office. KeyWords: Zone Price of Land, Land Office, Agrarian Law